The Impact of Immunotherapy on Sleep and Circadian Rhythms in Patients with Cancer - Balachandran, Diwakar D.; Bashoura, Lara; Sheshadri, Ajay; Manzullo, Ellen; Faiz, Saadia A. (Frontiers in Oncology, 2023)
Immunotherapy has revolutionized treatments for both early and advanced cancers, and as their role evolves, their impact on sleep and circadian rhythms continues to unfold. The recognition, evaluation, and treatment of sleep and circadian rhythm disturbance leads to improved symptom management, quality of life and treatment outcomes. An intricate complex relationship exists in the microenvironment with immunity, sleep and the tumor, and these may further vary based on the cancer, addition of standard chemotherapy, and pre-existing patient factors. Sleep and circadian rhythms may offer tools to better utilize immunotherapy in the care of cancer patients, leading to better treatment outcome, reduced symptom burden, and increased quality of life.